2019
DOI: 10.1002/mgg3.674
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive prenatal testing for fetal subchromosomal copy number variations and chromosomal aneuploidy by low‐pass whole‐genome sequencing

Abstract: Background Expanding noninvasive prenatal testing (NIPT) to include the detection of fetal subchromosomal copy number variations (CNVs) significantly decreased the sensitivity and specificity. Developing analytic pipeline to achieve high performance in the noninvasive detection of CNVs will largely contribute to the application of CNVs screening in clinical practice. Methods We developed the Noninvasively Prenatal Subchromosomal Copy number variation Detection (NIPSCCD) method based on low‐pass whole‐genome se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 38 publications
2
45
0
Order By: Relevance
“…As indicated above, it should be noted that our detection pipeline is capable of differentiating between a fetal CNV and a CNV from the mother (or the mother and the fetus). In a prospective setting, we noticed that very small aberrations are often calculated into the overall sensitivity [ 11 , 23 ] without evaluation of the z-score for the given aberration. We, therefore, assume that they would have been missed if they had not been maternal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated above, it should be noted that our detection pipeline is capable of differentiating between a fetal CNV and a CNV from the mother (or the mother and the fetus). In a prospective setting, we noticed that very small aberrations are often calculated into the overall sensitivity [ 11 , 23 ] without evaluation of the z-score for the given aberration. We, therefore, assume that they would have been missed if they had not been maternal.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al employed a Non-Invasively Prenatal Sub-Chromosomal Copy number variation Detection (NIPSCCD) algorithm and evaluated its performance on more than 20,000 clinical samples. The team achieved more than 90% sensitivity for CNVs of 5 Mb–10 Mb and 100% sensitivity for those ≥ 10 Mb with an average of 7.5 M sequencing tags [ 11 ]. Straver et al showed that 71.8% of CNVs ranging from 0.52 Mb to 84 Mb could be detected with as little as 3.5 M tags using the algorithm titled WISECONDOR (WIthinSamplE COpy Number aberration DetectOR), but with lower sensitivity (41.2% between 1 Mb and 5 Mb) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The common use of next-generation sequencing (NGS) and array comparative genomic hybridization (aCGH) in diagnostics has led to an increase of known pathogenic CNVs 10 . Thanks to the application of NIPT, fetal chromosomal aneuploidies subchromosomal abnormalities can be screening with high sensitivity and specificity 11,12 .…”
Section: Discussionmentioning
confidence: 99%
“…NIPT screening was performed as previous reported (Yu et al, ) at 17 weeks of gestation using the noninvasive prenatal subchromosomal copy number variation detection (NIPSCCD) method, which was low‐pass whole‐genome sequencing based approach.…”
Section: Methodsmentioning
confidence: 99%